Perceived effects of resettlement on the quality of life of selected families in Bistekville I, Quezon City - Guevara, Ronette Estrella D.; Chua, Consuelo T. (Quezon City College of Home Economics, University of the Philippines Diliman, 2017)
This study examined the perceived effects of resettlement on the quality of life of 30 families living in Bistekville I, Payatas, Quezon City. It also determined the current status of their quality of life according to these five domains: Satisfaction with Internal and External Family Relationships, Satisfaction with the Family's Basic Needs, Goal Attainment, Physical Health, and Emotional health. A quantitative instrument was used to measure the quality of life of the respondents. On the other hand, a qualitative research instrument was utilized to identify the perceived positive and negative effects of resettlement among the respondents. The data gathered were analyzed using descriptive statistics and content analysis. The results of the study showed that in general, the of the perceived quality of life of the respondents was very high. Specifically, the respondents displayed very high quality of life in terms of: satisfaction with their internal and external family relationships, physical health, goal attainment, and satisfaction with the family's basic needs. On the other hand, the respondents have a high satisfaction in the area of emotional health. Meanwhile, the positive perceived effects of resettlement on the quality of life of the respondents are better living conditions in terms of the physical and social environment, social cohesion through camaraderie and community involvement, better access to basic needs in terms of proximity to necessary establishments and personal utility connections among others. The negative perceived effects of resettlement on the quality of life of the respondents include: stress due to financial incapability to pay mortgage and taxes, and inadequate income to support the family.
Thesis Classification: F
Thesis (B.S. Home Economics)--University of the Philippines Diliman
Includes bibliographical references and appendices.
Keywords: Relocation (Housing) -- Philippines -- Qezon City